Sociocommunicative discourse of the ancient culture - Глотов, Олександр Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Literature as a social, psychological and educational phenomenon performed the function of the information channels in ancient Greek and Roman cultures until the emergence of the mass communication as a historical cultural and civilizational factor. The formation of a single society required the unity of the mentality, and this led to the acute socialization and politicization of the artistic word. Homer, Cicero, and Horace were the spokesmen of a distinct public order. Their texts formed a public opinion, and they were formed not because they were famous generals or state actors (although they were also them), not because they were rich or noble – no, because they were aesthetically convincing, logically unsurpassed and psychologically trustworthy. The master of the word could lose his personal battle for life, but he certainly won the war for the cause, for which he put his life in this glory, thus creating a definite social and communicative discourse. In this discourse, the person stands above the social because society consists of personalities. The person creates a community, rules it, changes it, if necessary – and this is supposed to be the main conquest of the entire ancient culture. The history of ancient literature is not confined solely to the confrontation and interaction of the main types of works of literature. The reason for its treatment is immeasurably more than purely artistic, emotional, and pragmatic, psychological and educational. The antique world, apparently, therefore, continues for a hundred years in a row to be a ground for the cultivation of as diverse as possible social as well as aesthetic ideas, which contains almost all versions of both artistic and socialcommunicative texts.